Progression of women to higher management positions in South African Public Sector : a differential effect of employment equity - Kanjere, Maria M; Ngwakwe, Collins C (Acta Universitatis Danubius Administratio, 2018)
This research examined the extend to which African women have progressed to top management positions in the public sector since the EE Act of 1998. The paper became apposite given the growing call for women inclusion in top management positions to enhance gender equity in South Africa. The paper applied a review approach coupled with a quantitative test to assess the level of difference before and after the gender equity act. Applying a t-test of difference in mean growth of progression to top positions before and after the EE Act review of 2013, results indicate that at P<0.001, a siginificant progress has been achieved African women progression to top management positions in the public sector since the enactment of the EE Act in 1998. However, it was noted that this progress has not been balanced as progress is slanting toward the sectors that are more prone to black economic empowerment (BEE) enablement. The paper recommends that in order to heighten a balanced progress, African women should strive to delve into other sectors that may not necessarily require the BEE enablement; this requires a continuous strive to acquire higher level education and technical skills to compete in all the sectors of South African industries.
Article published in the Acta Universitatis Danubius Administratio vol. 9, no. 2/2017, pp. 47-59
Keywords: Gender equity; African women; Employment equity; Discrimination; Women in top management.; Women-Employment re-entry; Women--Education--South Africa; Women--Social condition; Women executives-South Africa; Women-Emancipation